The wisdom of Thoth : magical texts in ancient Mediterranean civilisations - Bąkowska-Czerner, Grażyna; Bąkowska-Czerner, Grażyna; Roccati, Alessandro; Roccati, Alessandro; Świerzowska, Agata; Świerzowska, Agata (Archaeopress archaeology, 2015)
This volume represents a selection of contributions on Mediterranean themes from a wider international interdisciplinary conference on Magical Texts in Ancient Civilizations, organised by the Centre for Comparative Studies of Civilizations at Jagiellonian University in Krakow